Clinical and metabolic features of the randomised controlled Diabetes Remission Clinical Trial (DiRECT) cohort - Taylor, Roy (Diabetologia, 2017)
AIMS/HYPOTHESIS: Substantial weight loss in type 2 diabetes can achieve a return to non-diabetic biochemical status, without the need for medication. The Diabetes Remission Clinical Trial (DiRECT), a cluster-randomised controlled trial, is testing a structured intervention designed to achieve and sustain this over 2 years in a primary care setting to determine practicability for routine clinical practice. This paper reports the characteristics of the baseline cohort. METHODS: People with type 2 diabetes for <6 years with a BMI of 27–45 kg/m(2) were recruited in 49 UK primary care practices, randomised to either best-practice diabetes care alone or with an additional evidence-based weight management programme (Counterweight-Plus). The co-primary outcomes, at 12 months, are weight loss ≥15 kg and diabetes remission (HbA(1c) <48 mmol/mol [6.5%]) without glucose-lowering therapy for at least 2 months. Outcome assessors are blinded to group assignment. RESULTS: Of 1510 people invited, 423 (28%) accepted; of whom, 306 (72%) were eligible at screening and gave informed consent. Seven participants were later found to have been randomised in error and one withdrew consent, leaving 298 (176 men, 122 women) who will form the intention to treat (ITT) population for analysis. Mean (SD) age was 54.4 (7.6) years, duration of diabetes 3.0 (1.7) years, BMI 34.6 (4.4) kg/m(2) for all participants (34.2 (4.2) kg/m(2) in men and 35.3 (4.6) kg/m(2) in women) and baseline HbA(1c) (on treatment) 59.3 (12.7) mmol/mol (7.6% [1.2%]). The recruitment rate in the intervention and control groups, and comparisons between the subgroups recruited in Scotland and England, showed few differences. CONCLUSIONS/INTERPRETATION: DiRECT has recruited a cohort of people with type 2 diabetes with characteristics similar to those seen in routine practice, indicating potential widespread applicability. Over 25% of the eligible population wished to participate in the study, including a high proportion of men, in line with the prevalence distribution of type 2 diabetes. TRIAL REGISTRATION: www.controlled-trials.com/ISRCTN03267836; date of registration 20 December 2013